PROSES IMPLEMENTASI PROGRAM AKSEPTOR PRIA VASEKTOMI DI KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Johari Adi Wibowo E.42009074 (FISIP Universitas Tanjungpura Pontianak, 2021)
This research paper is written to describe a vasectomy in male acceptor programme as a policy implementation . this topic is choosen due to the problem of the programme that has been operating for a long period but it still ineffective and doesn't work maximal. This research using a qualitative approach that has been passed many step such as data collection, data analysis, and conclusion. the research locating at Sukadana subdistrict, Kayong Utara regency. the subject or this research is the government of Kayong Utara Regency who has a responsibility of the vasectomy programme, the participants of the programme in this case is a married men and some of public figure in Sukadana subdistrict. The conclusion of this research is there was some factors caused the programme was failed. the factors is there isn't any qualified medician either in Sukadana subdistrict Nd Kayong Utara regency. the people of Sukadana subdistrict think that it is a